Assessing the Status of Environmental Education in Illinois Elementary Schools - Rebecca M. Young; Sharron LaFollette (SAGE Publishing, 2009)
One-thousand Illinois elementary teachers received a survey intended to assess the amount and manner in which they included environmental education in the classroom during the 2005 academic year. Over 91% of respondents (n = 234) said that they taught about the environment at least once during the school year, yet most students were only exposed to 22 to 100 minutes during that year. Of the teachers that included environmental education, 49% said they did so because of personal interest in the environment; 47% of the teachers that excluded it said the reason was because of a lack of class time.